Penatalaksanaan Fisioterapi Pada KasusFrozen Shoulder DektraDi RSUD Sukoharjo - Wasiati, Dwi, Agus Widodo, SSt., Ft (2014)
Background: Frozen shoulder is a place for all disorders of the shoulder joint that causes pain and restriction of movement due to the scope of miofacial disorders with reduced mobility capsular pattern (eksorotasi> abduction> endorotasi. Primary complaint is that experienced a decrease in the strength of shoulder flexors and limitations LGS occurs actively or passively. Method: The method in handling such cases using infrared, manipulation and exercise therapy, which is evaluated by the method of measuring pain (VDS), measurement of muscle strength (MMT), with Goneometri LGS measurements, and functional ability with spadi. Objective: To determine whether there are benefits of physiotherapy in the management of cases of frozen shoulder to decrease pain, range of motion, increased muscle strength and functional ability in the case of Frozen Shoulder by using modalities Infrared, manipulation, and exercise therapy. Results: After treatment as much as 6 times the assessment showed a decrease in pain, increase in LGS, an increase in MMT, as well as increased functional ability. Conclusion: Infrared can reduce pain in the right shoulder in a state of Frozen Shoulder Dextra, manipulation can increase the range of motion in the right shoulder in the condition Dextra Frozen Shoulder, and Exercise Therapy can improve muscle strength and functional ability in the case of Dextra Frozen shoulder.